Spousal Presence as a Nonpharmacological Pain Management during Childbirth: A Pilot Study - Abigail U. Emelonye; Taina Pitkäaho; Katri Vehviläinen-Julkunen (Hindawi Limited, 2015)
Background. Measures of spousal effect during parturient pain should take a tripartite approach involving the parturients, spouses, and midwives. Aim. To develop and validate three questionnaires measuring spousal presence in management of parturient pain in Nigeria. Methods. There are two phases: (1) development of questionnaires, Abuja Instrument for Midwives (AIM), Abuja Instrument for Parturient Pain (AIPP), and Abuja Instrument for Parturient Spouses (AIPS), utilizing literatures, Kuopio instrument for fathers (KIF) and expertise of health professionals, and (2) pilot study to validate the questionnaires which were administered in two hospitals in Nigeria: midwives (n=10), parturients (n=10), and spouses (n=10).  Results. Internal consistency for the three questionnaires indicated Cronbach's alpha coefficient of 0.789 (AIM), 0.802 (AIPP), and 0.860 (AIPS), while test-retest reliability was r=0.99 (AIM), r=0.99 (AIPP), and r=0.90 (AIPS). Conclusions. AIM, AIPP, and AIPS provide a means of investigating the effectiveness of spousal presence in management of parturient pain in Nigeria. However, further testing of each instrument is needed in a larger population to replicate the beneficial findings of AIMS, AIPP, and AIPS which can contribute rigor to future studies.